Comparative Bioavailability Study of Jaspine B: Impact of Nanoliposomal Drug Delivery System on Pharmacokinetics - Biwash Ghimire; Pradeep Giri; Sameena Mateen; Srinath Pashikanti; Ali Aghazadeh-Habashi (Pharmaceutics, 2025)
Background/Objectives: Jaspine B, a synthetic analog of anhydrophytosphingosine, demonstrates significant anticancer activity; however, its clinical application is hindered by its poor oral bioavailability, resulting in suboptimal systemic exposure. This study aimed to enhance the pharmacokinetic properties of Jaspine B by developing a liposomal delivery system. Methods: Jaspine B-loaded liposomes were formulated using a microfluidic approach and characterized by transmission electron microscopy (TEM) to assess particle morphology and size distribution. A sensitive and selective LC-MS/MS assay was developed and fully validated to quantify Jaspine B in rat plasma. The assay revealed excellent linearity across a broad concentration range and high intra- and inter-day precision. A pharmacokinetic study was conducted in Sprague Dawley rats to evaluate the influence of liposomal encapsulation on the pharmacokinetic profile of Jaspine B. Results: The liposomal formulation accelerated the absorption of Jaspine B, reaching the maximum concentration (Tmax) at 2 h as opposed to 6 h in plain Jaspine B. The half-life (t1/2) increased significantly from 7.9 ± 2.3 h to 26.7 ± 7.3 h. The area under the curve (AUC0–∞) increased over two-fold from 56.8 ± 12.3 ng.h/mL to 139.7 ± 27.2 ng.h/mL, suggesting increased systemic drug exposure. Similarly, the drug molecule’s mean residence time (MRT) increased over three-fold. Conclusions: These results indicate that liposomal formulation enhances the pharmacokinetics of Jaspine B, prolonging its body circulation and exposure, which explains the improved therapeutic outcomes we observed in our previous pharmacodynamic study.